IMPROVING STUDENTS’ READING COMPREHENSION BY USING INQUIRYBASED LEARNING - Liza Oktarini (Linguists : Journal of Linguistics and Language Teaching, 2015)
This research was a classroom action research. The objective of this research was to explainwhether using Inquiry Based Learning Strategy can improve students’ reading comprehensionand factors improved the students’ reading comprehension at the 8A students of SMPN 7 KotaBengkulu. The subjects of this research were 32 students, consisted of 15 males and 17 females.The instruments of this research were reading comprehension tests, students’ and teacher’sobservation checklists and field notes and interview. The research was conducted into twocycles which included plan, action, observe, and reflect. The test was given at the end of eachcycle. The result of this research shows that using Inquiry Based Learning strategy improvedstudents’ reading comprehension. There were 34.37% of students passed the standard score>65 in cycle 1 and improved into 75% in cycle 2. The improvement was influenced by theInquiry Based Learning strategy, used of media and materials chosen and the teacher activitiesin the process of teaching and learning.